2022
DOI: 10.1002/adma.202204258
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Side‐Chain Hydrophilicity on Packing, Swelling, and Ion Interactions in Oxy‐Bithiophene Semiconductors

Abstract: the operation of a range of bioelectronic devices, [1][2][3] such as organic electrochemical transistors (OECTs), [4][5][6] batteries, [7] and supercapacitors. [6] They have inherent advantages over traditional organic semiconductors for these electrochemical applications, [4,[8][9][10] in particular their ability to operate with an aqueous electrolyte. [11,12] Exchanging a traditional alkyl-based side chain for a glycol-based hydrophilic side chain has been widely adopted as a strategy for increasing uptake o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 113 publications
0
27
0
Order By: Relevance
“…MD simulations were performed using a force field based on OPLS-AA, 49 with interthiophene dihedrals parametrized to fit with DFT at the B3LYP/6311G** level of theory. 50 Glycol side chain parameters are from work by Woods et al 51 and are based on OPLS-aa atom types, with other backbone bonded parameters from work by Moreno et al and Bhatta et al 52,53 The force field used is closely related to that presented in a recent MD simulation study of oxy-bithiophene oligomers by Siemons et al 54 All simulations were performed with 20-mers on a Au substrate, with Au parameters from work by Su et al 55 As a general procedure, all simulations begin with an in-vacuum energy minimization. Either single or multiple polymers are then placed 3 Å from the Au surface.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MD simulations were performed using a force field based on OPLS-AA, 49 with interthiophene dihedrals parametrized to fit with DFT at the B3LYP/6311G** level of theory. 50 Glycol side chain parameters are from work by Woods et al 51 and are based on OPLS-aa atom types, with other backbone bonded parameters from work by Moreno et al and Bhatta et al 52,53 The force field used is closely related to that presented in a recent MD simulation study of oxy-bithiophene oligomers by Siemons et al 54 All simulations were performed with 20-mers on a Au substrate, with Au parameters from work by Su et al 55 As a general procedure, all simulations begin with an in-vacuum energy minimization. Either single or multiple polymers are then placed 3 Å from the Au surface.…”
Section: Methodsmentioning
confidence: 99%
“…MD simulations were performed using a force field based on OPLS-AA, with interthiophene dihedrals parametrized to fit with DFT at the B3LYP/6311G** level of theory . Glycol side chain parameters are from work by Woods et al and are based on OPLS-aa atom types, with other backbone bonded parameters from work by Moreno et al and Bhatta et al. , The force field used is closely related to that presented in a recent MD simulation study of oxy-bithiophene oligomers by Siemons et al…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize cations in PgBT-(TriEG)2gTT films are chelated by the adjacent double trimeric ethylene glycol side chains positioned on each benzothiadiazole unit. 49 The differing EQCM behaviors between parent PgBT(F)-2gTT and derivatives PgBT(Ion)2gTT/PgBT(TriEG)2gTT contrast with their equivalent hydrophilicities, as determined through contact angle measurements (Figure S46, Table S2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…155 Siemons et al constructed an MD model to investigate the gradual exchange of hydrophobic alkyl-based side chains with hydrophilic EG-based side chains on polythiophenes. 160 The authors demonstrated that the oxygen content of the side chains influenced the packing behavior of the resulting OMIEC, where EG-based OMIEC was found to pack more effectively for charge transport in the solid state. Water was found to penetrate the OMIEC bulk through the π-stack (backbone) for the alkylated polymers and the lamellar stack (side chains) for the glycolated polymers.…”
Section: Characterization Of Mixed Transport Properties Of Oect Channelmentioning
confidence: 99%